Good Impression in Writing Business Correspondence by English as Foreign Language Students - Ramadhani, Putri (Forum Kerjasama Pendidikan Tinggi (FKPT), 2021)
This study concerned to investigate good impression in bussiness correspondence wriitten by by EFL (English as Foreign Language) students of second semester in Budi Darma University, Medan, North Sumatera-Indonesia, especially in writing application or cover letter. These EFL students were investigated to find out their capability to write appropriate application letter or usually called as cover letter. The problem found is the EFL students are failed to write good impression to the reader or employer. A writer should be able to make good impression about herself to the employer, because the essential point of writing application letter is how to impress the employer about a writer or a job seeker’s selling points. The writer found that most students need to be trained to write an application letter with good impression. This study focused on sixteen random students of the second semester in Budi Darma University Medan majored in Computer Engineering. The data was collected in August 2021. The data collection was conducted by assesing the samples of sixteen students’ writing test. The data was analyzed by using quantitative analysis to get the percentage of the students who were failed to write application letter with good impression to the reader. The results indicated that the students were less experience in writing application letter with good impression to the reader especially in personal touch it is how to write proper salutation and closing then followed by less experience in writing addressee and contact details. The suggestions are proposed to improve writing training to the students, the improvement of training to write application letter with good impression especially in personal touch and contact details